Fiber to the home (FTTH) activation system and analysis of dropcore cable connection losses on optical network performance - Asril, Aprinal Adila; Maria, Popy; Yustini, Yustini; setiawan, Herry; Nasrul, Nasrul (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The FTTH network is currently a reliable network concept used in an era where very fast access to information is needed as it is today, but several problems arise in the FTTH network, for example, reduced data transmission speed due to losses in the transmission cable connection or drop core. In this study, activation of the FTTH network will be carried out so that it can function for internet data transmission and observations will also be made of the connection losses on the 10-meter dropcore cable with the number of connections respectively, namely no connection, 1 connection, and 2 connections, where each connection obtains connection losses from 0.00 to 0.02 dB which will affect the total attenuation obtained in the activated FTTH network. Standard attenuation for fiber optic network activation starting from OLT to ONT according to IEEE Std 802.3ah states that the permissible attenuation / loss tolerance is between 20-24 to 29 dB. Splicing losses are caused by errors in the process of joining the fiber optic cable cores. The number of connections in a fiber optic cable can affect the attenuation value in the fiber optic cable. The more connections, the higher the attenuation in the fiber optic cable.